Excited state dynamics of the s-trans-1, 3-butadiene cation: an ab initio quantum dynamical analysis - Nikoobakht, Behnam; Dreuw, Andreas; Köppel, Horst (The journal of chemical physics, 2019)
The excited state dynamics of the s-trans-1,3-butadiene cation, focusing on the second and third bands of the photoelectron spectrum, have been investigated using a fully quantal approach, for the first time. The five lowest electronic states X2Bg, A2Au, B2Ag, C2Bu, and D2Ag considering the six vibrational modes S3, S5, S13, S17, S19, and S20 were taken into account in the nuclear quantum dynamical investigation. The potential energy curves have been calculated along these coordinates for the five lowest electronic states using the RS2C method. Our simulations indicate a moderately fast population transfer from the A2Au and B2Ag to the X2Bg state, taking place on a time scale of 70-80 fs. Furthermore, the computed second and third bands of the photoelectron spectrum are in good agreement with the corresponding experimental ones. Our calculation identifies the symmetric stretching of the central C—C bond S5 and the symmetric C—C—C bending S13 to be the main progression modes of the second and third bands of the photoelectron spectrum of (cationic) s-trans-1,3-butadiene.